Perioperative Sleep Disorder: A Review - Lin, Dandan; Huang, Xiao; Sun, Yi; Wei, Changwei; Wu, Anshi (Frontiers in Medicine, 2021)
Patients in the perioperative period usually present with different types and degrees of sleep disorders, which can severely affect their postoperative outcomes. Multiple risk factors may lead to the occurrence of perioperative sleep disorders, including personal factors, psychological factors, surgery factors, and environmental factors. In this review, we summarize the potential risk factors for perioperative sleep disorders during hospitalization. And it also provides an overview of perioperative outcomes and potential therapeutic prevention of perioperative sleep disorders. However, more researches are necessary to investigate the effectiveness and safety of preventions in the clinical practice and push forward the therapies.